Multiple Halogenation of Aliphatic C−H Bonds within the Hofmann–Löffler Manifold - Del Castillo, Estefanía (2018)
An innovative approach to position-selective polyhalogenation of aliphatic hydrocarbon bonds is presented. The reaction proceeded within the Hofmann-Löffler manifold with amidyl radicals as the sole mediators to induce selective 1,5- and 1,6-hydrogen-atom transfer followed by halogenation. Multiple halogenation events of up to four innate C−H bond functionalizations were accomplished. The broad applicability of this new entry into polyhalogenation and the resulting synthetic possibilities were demonstrated for a total of 27 different examples including mixed halogenations.